A novel energy-saving and emission-reduction strategy based on facile preparation of thermal insulation coatings doped with modified vacuum ceramic microbeads for concrete protection - Lanxin Wang; Yang Li; Fengjuan Wang; Zhiyong Liu; Jinyang Jiang (Journal of Materials Research and Technology, 2024)
The development of thermal insulation protective coatings suitable for constructions and buildings offers a multifaceted approach: it substantially reduces indoor temperatures, enhances residential comfort, decreases air conditioning energy consumption, and conserves energy. Additionally, these coatings provide robust resistance against corrosive substances, thereby significantly prolonging the service life of concrete. In this work, the modification of vacuum ceramic microbeads (VCM) through the polymerization of catechol and hexamethylene diamine to form poly(catecholamine) (PCA) was investigated by FT-IR, XRD, and TEM analysis. Increased levels of incorporation of VCM@PCA further decreased thermal conductivity and increased surface hydrophobicity, while excessive incorporation detrimentally affected the coating's mechanical properties. PDMS/VCM@PCA coating demonstrated exceptional thermal insulation performance, reducing coating temperature by 15.9 °C under simulated sunlight exposure, and in outdoor experiments, the interior temperature of the simulated house with this coating was 4.2 °C lower than the external temperature, highlighting its potential for energy conservation, emission reduction, and building temperature regulation. Additionally, PDMS/VCM@PCA coating provided excellent protection for concrete structures, significantly enhancing abrasion resistance. It also improved the interfacial adhesion between the organic layer and concrete under dry, wet, and 10% NaCl immersion conditions. The addition of VCM@PCA further enhanced resistance to chloride ion penetration, effectively reducing chloride ingress. This thermal insulation protective coating presents a novel strategy for energy conservation, emission reduction, and sustainable development in the civil construction industry.